Nutrients Quality of Fermented Complete Feed Based on By-Product of Sago (Metroxylon sp.) and Cassava (Mannihot esculenta Cranz) - Masitah, Siti (clo Convention Linkage, Inc., 2016)
Sago (Metroxylon sp.) was grown in the tropics and well-adapted on peat and swampy soil (Melling et al., 2005). The largest supply of sago comes from the South East Asia, particularly Indonesia and Malaysia. The trunk of sago tree may reach 3 to 5 cm in diameter at 24 months and may grow until 20 m tall (Bintoro et al., 2010). The main product of sago is the starch, which is extracted from the spongy center of sago’s trunk and produced sago dregs as the by-product. Another by-product from sago is the leaves. In the past, sago leaves were commonly used to make roof, but nowadays people do not use sago roof anymore, thus the leaves were throw away and considered as waste. Cassava (Mannihot esculenta Cranz) is another main agricultural product in Indonesia. Cassava mainly planted for its tuber, and left the leaves as by-product. Cassava tuber is a good energy source, while the leaves contain high crude protein (CP) which is ranged from 20 to 36% (Askar, 1996). Leaves of sago and cassava may be used as fiber sources in ruminant feeding, while sago dregs and cassava tuber can used as energy source. Cassava (Mannihot esculenta Cranz) is another main agricultural product in Indonesia. Cassava mainly planted for its tuber, and left the leaves as by-product. Cassava tuber is a good energy source, while the leaves contain high crude protein (CP) which is ranged from 20 to 36% (Askar, 1996). Leaves of sago and cassava may be used as fiber sources in ruminant feeding, while sago dregs and cassava tuber can used as energy source